Metabolically healthy obesity is associated with an increased risk of diabetes independently of nonalcoholic fatty liver disease. Issue 9 (30th July 2016) - Chang, Yoosoo; Jung, Hyun‐Suk; Yun, Kyung Eun; Cho, Juhee; Ahn, Jiin; Chung, Eun Chul; Shin, Hocheol; Ryu, Seungho
Abstract : Objective: This study examined whether the metabolically healthy obesity (MHO) phenotype was associated with an increased risk of diabetes in a large cohort of metabolically healthy individuals and whether that association differed by presence of nonalcoholic fatty liver disease (NAFLD). Methods: The cohort consisted of 74, 509 Korean adults who were metabolically healthy at baseline, defined as not having any metabolic syndrome component except large waist circumference and having homeostasis model assessment of insulin resistance <2.5. NAFLD was defined as hepatic steatosis on ultrasonography in the absence of excessive alcohol use or any other identifiable cause. Results: Over 304, 852.6 person‐years of follow‐up, 472 participants developed diabetes (incidence density, 1.5 per 1, 000 person‐years). The multivariable‐adjusted hazard ratios (95% confidence intervals) for incident diabetes in subjects with overweight and obesity compared with subjects with normal weight were 1.29 (1.00–2.16) and 1.57 (1.14–2.16), respectively, for subjects without NAFLD and 1.90 (0.95–3.80) and 2.57 (1.32–5.02), respectively, for those with NAFLD ( P for interaction =0.57). Conclusions: In this metabolically healthy population, individuals with overweight and obesity exhibited an increased incidence of diabetes, regardless of the presence of NAFLD. This finding suggests that the obese phenotype per se, independent of the presence of NAFLD, can increase the development of diabetes.